Communication Structuring in Aisyiyah’s Empowerment Activities in Isolated Tribal Communities - Erwin Rasyid; Fitri Maulidah Rahmawati; Hari Akbar Sugiantoro (Universitas Muhammadiyah Yogyakarta, 2022)
Several parties continue to criticize the empowerment of remote tribal or indigenous communities. The empowerment program for remote indigenous communities has not yet been deemed effective for empowering indigenous communities. Using Anthony Giddens’ structuration theory, this study aims to examine how communication is structured in community empowerment activities for isolated tribes. Using a case study methodology, this study uses qualitative descriptive approach. Interviews were conducted with the Regional Leader of ‘Aisyiyah (PDA) Banggai, who empowered an isolated tribe in the interior of Tombiobong, Maleo Jaya village, South Batui sub-district, Banggai district, Central Sulawesi (Sulteng). The study indicates that social reproduction occurs through the duality of structures in Aisyiyah empowerment activities among the indigenous Loinang people. This fits with Giddens’s idea of duality, which says that structure and agent work together and affect each other.